UPAYA PERLINDUNGAN HUKUM OLEH KOMNAS PEREMPUAN TERHADAP KORBAN KEJAHATAN SEKSTORSI DI DUNIA MAYA - Elfira Valentina Febriani; Aji Wibowo (Fakultas Hukum Universitas Tarumanagara, 2022)
Sextortion is an act of sexual exploitation by the perpetrator by abusing the power or authority tocarry out sexual acts, pictures, or videos of the victim. For example, threats or acts of spreadingnon-consensual intimate content followed by extortion such as forcing the victim to pay a sum ofmoney, having sex, or providing more intimate content. This study discusses the legal protectionef orts provided by the state to victims of sextortion in cyberspace based on ‘positif’ law inIndonesia and legal protection ef orts provided by Komnas Perempuan against victims ofsextortion in cyberspace. The research is categorized as a normative research with document studyor library research as data collected technique and the data analysis used in this research isqualitative analysis. Based on the results, the preventive legal protection ef orts provided by thestate to victims of cyber-sex crimes based on ‘positif’ law in Indonesia is formulated in theCriminal Code, the ITE Law, and the Pornography Law. Meanwhile, the repressive legalprotection ef orts provided by the state are embodied in the Witness and Victim Protection Law inthe form of: rights to assistance and restitution. There are also legal protection ef orts provided byKomnas Perempuan to victims of sextoration crimes in cyberspace that are in accordance with themandate of Komnas Perempuan contained in Presidential Regulation No. 65 of 2005, such asencouraging the legalisation of appropriate policies to deal with sextors, such as the TPKS Billand facilitate victims to the service providers in accordance with the victims’ needs.